The effect of a proposed training program using intermittent Training method on some of the physical qualities during physical preparation phase for football players junior under 19 years old - Douida , kaiss; Boureghda Mohamed, Messaoud (sports creativity, 2025)
This study aims to identify the effect of a proposed training program using intermittent Training method on some physical qualities during physical preparation phase for football players junior under 19 years old, the researcher has chosen thirty (30) football players from Najm BENI OULBANE Club, under the age of 19. The sample is divided randomly into two groups (controlled and experimental). Each group consists of 12 players, while the remaining 6 players were picked out for the exploratory experience, using the experimental method for this study. Our study was based on three physical tests : Transitional speed test ( 10m, 20m, 30m from high start ) - Vertical jump test ( Sargent test ) - YO-YO endurance intermittent test . After applying the proposed program in six ( 6 ) weeks on the experimental group, we obtained the results that we statistically treated with SPSS . the results were as follows : The proposed training program affected positively on football players' physical qualities during the physical preparation phase. We conclude that there are statistical differences between pre and post tests in benefit of the experimental group in terms of transitional speed and strength characterized by speed as well as enduranc